Desarrollando una óptica queer: coloquio con David William Foster. - Holcombe, W. Daniel (Studies in Latin American Popular Culture, 2012)
Queer theory, ever-changing, mutable, and deconstructive, facilitates the investigation of cultural production in a manner distinct from lesbian, bisexual, and gay "lesbigay" studies. Queer theories or theorizations (as compared to the current use of feminisms) present unique approaches to critical analysis, thereby providing investigators with an opportunity to analyze popular culture in a new light. This essay shows how queer theories may be applied to the analysis of Spanish language cultural production, presenting certain complex themes that question preconceived ideas as regards subjective identities and social norms. The transatlantic perspective of David William Foster's focus on Hispanic cultural production in the United States, Latin America, and Spain highlights die subjectivity of the concept of nationality. Inspired by the works of Foucault, Doty, Jagose, Halperin, and Dollimore, among others, Foster continues to engender his own space within queer theories and Spanish language popular culture criticism. This series of conversations with Foster between June 2009 and May 2011 will guide those interested in investigating cultural production based on the rubrics of queer theories to develop a working knowledge of what constitutes a queer Hispanic agenda, thereby forming a series of internal reflections that may help combat prejudice and homophobia.